The Unfolded Protein Response and Autophagy on the Crossroads of Coronaviruses Infections - Prestes, Elisa B.; Bruno, Julia C. P.; Travassos, Leonardo H.; Carneiro, Leticia A. M. (Frontiers in Cellular and Infection Microbiology, 2021)
The ability to sense and adequately respond to variable environmental conditions is central for cellular and organismal homeostasis. Eukaryotic cells are equipped with a set of highly conserved stress-response mechanisms that support cellular function when homeostasis is compromised, promoting survival. Two such mechanisms – the unfolded protein response (UPR) and autophagy – are involved in the cellular response to perturbations in the endoplasmic reticulum, in calcium homeostasis, in cellular energy or in redox status. Each of them operates through conserved signaling pathways to promote cellular adaptations that include re-programming transcription of genes and translation of new proteins and degradation of cellular components, respectively. In addition to their specific functions, it is becoming increasingly clear that these pathways intersect in many ways in different contexts of cellular stress. Viral infections are a major cause of cellular stress as many cellular functions are coopted to support viral replication. Both UPR and autophagy are induced upon infection with many different viruses with varying outcomes – in some instances controlling infection while in others supporting viral replication and infection. The role of UPR and autophagy in response to coronavirus infection has been a matter of debate in the last decade. It has been suggested that CoV exploit components of autophagy machinery and UPR to generate double-membrane vesicles where it establishes its replicative niche and to control the balance between cell death and survival during infection. Even though the molecular mechanisms are not fully elucidated, it is clear that UPR and autophagy are intimately associated during CoV infections. The current SARS-CoV-2 pandemic has bought renewed interested to this topic as several drugs known to modulate autophagy – including chloroquine, statins, niclosamide, valinomycin and cathepsin inhibitors – were proposed as therapeutic options. Their efficacy is still debatable, which highlights the need to better understand the molecular interactions between CoV, UPR and autophagy.